1998
DOI: 10.1103/physrevc.57.3225
|View full text |Cite
|
Sign up to set email alerts
|

Coulomb dissociation of light nuclei

Abstract: We present an alternative theoretical formulation of the Coulomb dissociation process. We apply the formalism to the deuteron as an example of a weakly bound two-body composite nucleus with a charged core and a neutral valence particle and for which exclusive experimental data exist in an appropriate kinematical regime. The theoretical scheme assumes that the projectile excitation is predominantly to states with low internal energy and is expected to be applicable at incident projectile energies of tens of MeV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
60
0
2

Year Published

1999
1999
2010
2010

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(63 citation statements)
references
References 25 publications
1
60
0
2
Order By: Relevance
“…Following the theories in [3], we present finite range quantum mechanical calculations of elastic Coulomb breakup of the halo nuclei 6 He and 19 C, which allow the use of realistic wave functions. We assume that the excitation of the projectile can be treated adiabatically, i.e.…”
mentioning
confidence: 99%
“…Following the theories in [3], we present finite range quantum mechanical calculations of elastic Coulomb breakup of the halo nuclei 6 He and 19 C, which allow the use of realistic wave functions. We assume that the excitation of the projectile can be treated adiabatically, i.e.…”
mentioning
confidence: 99%
“…At the same time, the asymmetric spectrum shape suggests contributions from higher partial waves, post-acceleration effects, and/or interference with the nuclear breakup. A "pure-Coulomb" calculation in the framework of adiabatic approximation [3], for example, roughly accounts for the tendency of data but does not reproduce the distinctive difference between 208 Pb and other targets. This time the data should be truly useful to establish a theoretical treatment of Coulomb-breakup of loosely bound projectiles.…”
Section: Resultsmentioning
confidence: 99%
“…They concluded that the nuclear breakup was more dominant for the heaviest targets. This data has been validated by modern 3-body theories [22]; however, these models have not yet been demonstrated to work at lower energies. The role of Coulombic and nuclear breakup is clearly changing in this energy region and systematic measurements are needed.…”
Section: Neutron Production By Deuteron Breakupmentioning
confidence: 99%